Solar Power Generator as an Alternative Energy Source for the Propeller Driver Motor - Hermanto, Andy Wahyu; Dzulfiqor, Achmad (RSF Conference Series: Engineering and Technology, 2023)
Solar Power Generation is one of the renewable energy modes currently being extensively developed. This is due to environmental issues caused by non-environmentally friendly fossil fuel sources. The purpose of this research is to support efforts in reducing the use of fossil fuels by designing a model of an electric main engine using Solar Power Generation (PLTS) and understanding the working system of this design. The research method used is the Research and Development method, consisting of 10 stages. These stages include information gathering, product planning, initial product form development, initial testing, initial revisions, main testing, major revisions, testing and validation, final revisions, and product implementation. The results of this research include designing the model, starting with assembling electronic and mechanical components and integrating them into the ship’s body as a system. The working system of this design involves converting solar energy into electrical energy, which is then used as the energy source to drive the ship’s propeller.